Olbrzymiokomórkowe zapalenie tętnic – opis przypadku - Napora, Katarzyna; Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Giant cell arteritis is a systemic disease of unknown origin. Vasculitis involves large and medium-sized vessels. Frequent clinical manifestations include characteristic headache in the temporal area , jaw or tongue claudication, apathy, fatigue, weight loss. The incidence of ocular involvement is reported in up to 70% patients. The most common and serious ophthalmic presentation is arteritic anterior ischemic optic neuropathy, which can lead to irreversible visual loss. Only early and aggressive steroid therapy may prevent this dangerous complication. The authors presented a case of a 68 years old woman with giant cell arteritis. The main visual manifestation of this disease was anterior ischemic optic neuropathy.